Race, Sex Work and Ethnographic Representation or, What To Do About Loki’s Toast - Kane, Stephanie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
This essay shifts the focus of analysis away from the folk poetry text itself and toward the politics of text collection and academic knowledge production. The content of an African American toast, told to the author in Chicago, is used to interrogate the grounds of race, gender and class differentials upon which art and experience are constructed.